(untitled) (Diversification: Journal of Economics and Management Studies, 2024)
The background of the research is based on the formulation of the problem, namely the challenges faced by the Learning Activity Studio (SKB) in Medan City from the perspective of training management due to limited resources. This study uses a qualitative approach with a descriptive analysis method. The subjects in this study are leaders and employees at SPNF SDKB in Medan City who are selected through purposive sampling techniques. Data collection was carried out through observation and interviews directly to respondents. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the analysis show that the development of human resources in a SKB is very necessary to improve the quality and success of the training program, namely further efforts are needed in the development of more varied training programs and more activities, as well as improving human resource competencies so that the company can survive and develop in accordance with environmental demands. To increase training management resources, SKB can consider strategies such as internal and external training, as well as the use of technology to improve training access and efficiency. SKB also needs to increase the role and participation of the community in the process of training and human resource development to increase public awareness and involvement in human resource development.